Implementation of Digital Marketing Strategy for the Development of Spiritual Tourism in Bali Province - I Komang Arif Ariyadi; Ni Putu Nina Eka Lestari (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
This research aims to explore the application of digital marketing strategies in the development of spiritual tourism in Bali Province, with a focus on the Griya Taman Beji Waterfall. By analyzing the role of social media in influencing tourist behavior and preferences, this research provides insight into the potential and challenges in promoting spiritual tourism in Bali. Through case studies involving interviews with managers, tour guides, and tourists, findings show that digital marketing, particularly through social media platforms such as Instagram, TikTok, and Facebook, has helped increase exposure and interest in Griya Taman Beji. The use of visual content and comprehensive information about tourist sites, as well as the involvement of local communities as tourist guides, also play an important role in attracting visitors. Thus, the conclusions of this research confirm the importance of digital marketing strategies in the development of spiritual tourism in Bali, while offering suggestions for improving digital marketing at Griya Taman Beji Waterfall through better collaboration with local stakeholders and in-depth research on digital marketing concepts in the Province Bali.Keywords: digital marketing, spiritual tourism, Bali, social media